Acceptance of augmented reality for laboratory safety training: methodology and an evaluation study - Ismael, Muhannad; McCall, Roderick; McGee, Fintan; Belkacem, Ilyasse; Stefas, Mickaël; Baixauli, Joan; Arl, Didier (Frontiers in Virtual Reality, 2024)
This paper presents a proof-of-concept Augmented Reality (AR) system known as "SMARTLab", for safety training in hazardous material science laboratories. The paper contains an overview of the design rationale, development, methodology, and a user study. Participants of the user study were domain experts (i.e., actual lab users in a material science research department, n=13) and the evaluation used a questionnaire and free form interview responses. The participants undertook a virtual lab experiment, designed in collaboration with a domain expert. While using the AR environment they were accompanied by a virtual assistant.The user study provides preliminary findings about the impact of multiple dimensions, such as Performance Expectancy, Emotional Reactivity and Spatial Presence, on SMARTLab acceptance by analyzing their influence on the Behavioral Intention dimension. The findings indicate that users find the approach useful and that they would consider using such a system. Quantitative and qualitative analysis of the SMARTLab assessment data suggests that a) AR based training is a potential solution for laboratory safety training without the risk of real world hazards, b) realism remains an important property for some aspects such as fluid dynamics and experimental procedure, and c) use of a virtual assistant is welcome and provides no sense of discomfort or unease. Furthermore, the study recommends the use of AR assistance tools (a virtual assistant, an attention funnel and an in-situ arrow) to improve usability and to make the training experience more user friendly.